Novel designs and theories for holographic fiber networking components. - Yun, Gang. (University of Ottawa (Canada), 1993)
The author's major contributions presented in this Ph.D. thesis are three novel design techniques (or concepts) for implementation of efficient holographic fiber networking components. The first concept is termed grating degeneration, which allows sharing of one holographic grating by more than one wave pair. This makes it possible to use a single grating as a number of 2 x 2 couplers in parallel, and the number of gratings required for fiber N x N couplers can be significantly reduced. The second concept is the so-called sandwich structure. By using a sandwich structure, a multi-stage topology, instead of a complete mesh, can be incorporated in the construction of a grating system in a coupler. This again can simplify the structure of an N x N coupler, especially when combined with the grating degeneration technique. The third technique, called quasi-Bragg diffraction is introduced in this thesis for the construction of 16 x 16 couplers. It turns out that when designed properly, the number of gratings required by a 16 x 16 coupler can be reduced to two per slab. The key technique is to use off-Bragg diffraction while keeping the violation of Bragg condition much higher for the unwanted waves than for the wanted waves. This technique may also be applied to other grating-based components. More generally, all of the three presented techniques may be applied to any multiple-grating-based component. An example is given in this thesis for applying grating degeneration to the construction of 8 x 8 wavelength routing couplers. Another aspect of the author's contribution is the development of a generalized diffraction theory. The major features of the theory are the rigorousness and the generality. On one hand, the theory is rigorously based on Maxwell's equations, which makes it a realistic model for simulations and analyses. On the other hand, the theory places no restrictions on light polarization, the incident wave direction and the parameters of the grating system. This is vital to the design of a multi-grating system using grating degeneration because of the three-dimensional arrangement of the wave vectors. Jones matrices are used for a complete characterization of any grating-bearing slabs. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.